Drivers of Economic Growth in Nepal: The Role of Economic Globalization, Inflation, Capital Formation, and Demographic Pressure - Dahal, Arjun Kumar; Budhathoki, Prem Bahadur; Bhattarai, Ganesh (Adhyayan Journal, 2026)
This study aims to evaluate the influence of economic globalization, inflation rate, gross capital formation, and age dependency ratio on Nepal's economic growth. It relies on secondary data of 55 annual data points from 1970 to 2024. An analytical research design is employed. The autoregressive distributed lag (ARDL) model is employed to examine the short-term and long-term impact of independent variables on the dependent variable. Approximately 70 percent of the fluctuation in Nepal's economic growth is attributed to economic globalization, inflation rates, total capital formation, and the age dependency ratio. The findings demonstrate that a one percent variation in total capital formation and the inflation rate yields a 1.336 percent and 0.236 percent enhancement in economic growth, respectively. Economic globalization and the age dependence ratio exert no major individual influence on economic growth. Nepal ought to implement a balanced policy framework that stimulates capital investment via public–private partnerships, directs remittances into productive sectors, sustains stable and manageable inflation, generates employment and skills training to leverage the demographic dividend, reinforces pension systems, and improves global integration through enhanced institutions, trade logistics, and regional agreements.